Parental emotions in families of children and adolescents with and without autism spectrum disorder - Gustavo Correia Basto da Silva; Ramon Targino Firmino; Ana Beatriz Dantas Nogueira; Andreza Cristina de Lima Targino Massoni; Sérgio D'Ávila (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract: This study assessed the influence of sociodemographic conditions, oral hygiene habits, and the socio-psychological need for orthodontic treatment on the emotions of caregivers of children with and without autism spectrum disorder (ASD). We conducted a comparative cross-sectional study with families of individuals aged 6 to 14 years at a reference center for neurodevelopmental disorders and two dental school clinics in northeastern Brazil. Caregiver emotions were assessed using the 'Parental Emotions' domain of the Family Impact Scale (FIS). We analyzed sociodemographic variables, oral hygiene habits, and sociopsychological need for orthodontic treatment using the esthetic component of the Index of Orthodontic Treatment Need (IOTN). We used descriptive and hierarchical Poisson regression analyses with robust variance (α = 5%). The study included 144 families evenly distributed across the groups. The caregiver group with ASD demonstrated a higher total score for parental emotions (p < 0.001). Factors associated with this factor included caregiver responsible for brushing (PR = 1.34; 95%CI: 1.12-1.59), mandatory need for orthodontic treatment (PR = 1.25; 95%CI: 1.07-1.46), and caregivers' education up to 8 years (PR = 1.45; 95%CI: 1.02-2.07). Caregivers with lower income showed a lower prevalence of parental emotions (PR = 0.57; 95%CI: 0.35-0.93). Caregivers of children with ASD exhibited a higher emotional burden. Factors associated with parental emotions included responsibility for tooth brushing attributed to caregivers, sociopsychological need for orthodontic treatment, and family income.